Employees compensation : a Singapore perspective. - Qiu, Jiahui. (2008)
This research study seeks to examine the different aspects of employees compensation from a Singapore perspective. In particular, the importance of non-monetary incentives, Flexible Wage System, Flexible Benefits Scheme, and the preferences of the type of incentives employees would prefer with regards to demographics are investigated.